Mice Heterozygous for the Oxytocin Receptor Gene (Oxtr+/−) Show Impaired Social Behaviour but not Increased Aggression or Cognitive Inflexibility: Evidence of a Selective Haploinsufficiency Gene Effect. (24th January 2013) - Sala, M.; Braida, D.; Donzelli, A.; Martucci, R.; Busnelli, M.; Bulgheroni, E.; Rubino, T.; Parolaro, D.; Nishimori, K.; Chini, B.
<x xml:space="preserve">Abstract</x> We characterised the behavioural phenotype of mice heterozygous (Oxtr+/−) for the oxytocin receptor gene (Oxtr) and compared it with that of Oxtr null mice (Oxtr−/−), which display autistic‐like behaviours, including impaired sociability and preference for social novelty, impaired cognitive flexibility, and increased aggression. Similar to Oxtr−/− mice, the Oxtr+/− showed impaired sociability and preference for social novelty but, unlike the null genotype, their cognitive flexibility and aggression were normal. By autoradiography, Oxtr+/− mice were found to have approximately 50% fewer oxytocin receptors (OXTRs) in all of the examined brain regions. Thus, because a partial reduction in Oxtr gene expression is sufficient to compromise social behaviour, the Oxtr acts as a haploinsufficient gene. Furthermore, the inactivation of the Oxtr gene affects specific behaviours in a dose‐dependent manner: social behaviour is sensitive to even a partial reduction in Oxtr gene expression, whereas defects in aggression and cognitive flexibility require the complete inactivation of the Oxtr gene to emerge. We then investigated the rescue of the Oxtr+/− social deficits by oxytocin (OT) and Thr4Gly7OT (TGOT) administered i.c.v. at different doses. TGOT was more potent than OT in rescuing sociability and social novelty in both genotypes. Furthermore, the TGOT doses that reverted impaired sociability and preference for social novelty in Oxtr+/− were lower than those required in Oxtr−/−, thus suggesting that the rescue effect is mediated by OXTR in Oxtr+/− and by other receptors (presumably vasopressin V1a receptors) in Oxtr−/−. In line with this, a low dose of the selective oxytocin antagonist desGlyDTyrOVT blocks the rescue effect of TGOT only in the Oxtr+/− genotype, whereas the less selective antagonist SR49059 blocks rescue in both genotypes. In conclusion, the Oxtr+/− mouse is a unique animal model for investigating how partial loss of the Oxtr gene impair social interactions, and for designing pharmacological rescue strategies.